Molecular Dynamics Simulation Study on Fluorine Plasma Ion Implantation in AlGaN/GaN Heterostructures - Li Yuan; Wang, Maojun; Chen, Kevin J. (2008 9TH INTERNATIONAL CONFERENCE ON SOLID-STATE AND INTEGRATED-CIRCUIT TECHNOLOGY, VOLS 1-4, 2008)
Fluorine plasma ion implantation is a robust technique that enables shallow implantation of fluorine ions into group III-nitride epitaxial structures. This technique has been used to achieve robust threshold control of the AlGaN/GaN high electron mobility transistors (HEMTs) and. led to the realization of self-aligned enhancement-mode devices. To reveal the atomic scale interactions and provide a modeling tool for process design and optimization, a molecular dynamics (MD) simulation is conducted for carbon tetrafluoride (CF(4)) plasma implantation. Specific potential functions are applied to calculate the interactions among atoms and simulate the dynamics process of fluorine ions' penetration and stopping in III-nitride materials. The MD simulation provides accurate information on dopant profiles that are verified by secondary ion mass spectrum (SIMS) measurements. Defect formation and distributions, that are critical in process development, are also investigated. The MD simulation tool is capable of providing 2-dimensional fluorine dopant profiles.